2022
DOI: 10.1002/joc.7599
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of aerosol types and their vertical distribution over East Asia based on CALIPSO lidar measurements

Abstract: Aerosol vertical distribution generally determines their health impacts and climate effects. By using long‐term (2007–2019) CALIPSO lidar measurements, we present a large‐scale insight into the climatology of aerosol types and their vertical structure over East Asia. Despite the low sampling frequency, comparison with MODIS aerosol optical depth (AOD) shows that the integrated CAIPSO vertical extinction can reasonably reproduce spatial patterns of the aerosol loading. With the unique advantage of active detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In general, the vertical distribution of aerosols dictates their health and climate implications [ 91 ]. The vertical profiles of the occurrence frequencies of the aerosol subtype layers observed in the daytime and nighttime over the Aral Sea region in different seasons are shown in Figure 5 , Figure 6 , Figure 7 , Figure 8 and Figure 9 .…”
Section: Resultsmentioning
confidence: 99%
“…In general, the vertical distribution of aerosols dictates their health and climate implications [ 91 ]. The vertical profiles of the occurrence frequencies of the aerosol subtype layers observed in the daytime and nighttime over the Aral Sea region in different seasons are shown in Figure 5 , Figure 6 , Figure 7 , Figure 8 and Figure 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, measurements of the attenuated backscatter and depolarization ratio can be used to identify the type of aerosols and clouds based on position, height, and surface types [32]. CALIPSO, in combination with other satellites in A-Train, can effectively detect the vertical structure and characteristics of clouds and aerosol layers [33]. Version V4.1 L2 CALIPSO aerosol products have been significantly improved in terms of extinction, optical depth [34], and aerosol classification [35].…”
Section: Calipsomentioning
confidence: 99%
“…At regional scale, the CALIOP data show that AOD at nighttime is larger than that in the daytime over eastern China (Gui et al, 2022;Huang et al, 2013) and the North China Plain (Xu et al, 2019). The larger nighttime AOD is ascribed to weaker convection and diffusion caused by lower temperature at night (Gui et al, 2022), greater hygroscopic growth of aerosols at low levels at nighttime than during the day (Xu et al, 2019), and undetected daytime low aerosol concentrations at high levels caused by solar radiation interference (Xu et al, 2019). In contrast, Su et al (2020) found that CALIOP AOD is larger during the daytime than at night over northeastern China and hypothesized that this difference is caused by greater anthropogenic emissions during the day than at night.…”
Section: Introductionmentioning
confidence: 99%
“…The factors in these large differences have not been investigated with rigor. At regional scale, the CALIOP data show that AOD at nighttime is larger than that in the daytime over eastern China (Gui et al., 2022; Huang et al., 2013) and the North China Plain (Xu et al., 2019). The larger nighttime AOD is ascribed to weaker convection and diffusion caused by lower temperature at night (Gui et al., 2022), greater hygroscopic growth of aerosols at low levels at nighttime than during the day (Xu et al., 2019), and undetected daytime low aerosol concentrations at high levels caused by solar radiation interference (Xu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%